The Role of Mindfulness and Assertiveness on Housewives’ Marital Satisfaction - Zalki, Riki; Sampe Tondok, Marselius (Kuras Institute, 2024)
Housewives are frequently burdened with numerous roles and responsibilities, occasionally contending with domestic conflicts that impact their level of marital satisfaction. The purpose of this study was to find out the role of mindfulness and assertiveness in the marital satisfaction of housewives who do not have a job. This research was a quantitative survey research on 262 unemployed housewives. Participants were selected using purposive sampling. Three scales were used to collect data the Marital Satisfaction Scale, the Mindfulness Scale, and the Assertiveness Scale. Data for hypothesis testing were analyzed using multiple regression. The results revealed that mindfulness and assertiveness have a positive and significant role in affecting housewives’ marital satisfaction at 29.4 percent. The implication of this study is that improving mindfulness and assertiveness among housewives, particularly those who prioritize household responsibilities and do not work, can positively influence marital satisfaction.